PEMIKIRAN HUKUM HAZAIRIN - WAHIDAH WAHIDAH (Syariah: Jurnal Hukum dan Pemikiran, 2015)
Hazairin is an intellectual of Islamic law. Although most of his live and education are incommon education, not in speciality of islamic way, but Islam that was learned autodidactly makes hebecoming a great man as modern islamic reformer. He concluded that social system in what Quranwants is not a clan system or anti-unilaterality. In one side, seriousness of thinking that was produced byHazarin is considered as controversial statement. In the other side, his recent breakthrough has beenrealized through a number of Law rules.